"Everyone has the ability actualy to do well in education. It's just the support mechanisms that you give to them…": A systematic literature review exploring the educational experiences of children in care. (June 2022) - Goding, Natasha; Hartwell, Brettany; Kreppner, Jana
Highlights: Children in Care can experience stigma and a limited understanding of the impact of care on their educational experiences. Children in Care perceive the quality of their relationships as key to engagement and progress in education. Support valued by Children in Care includes access to leisure and sport activities and safe spaces. Children in Care wish for their views to be sought and to have increased agency in their educational experiences. Abstract: The educational outcomes and attainment of children and young people in care (CYPIC) are lower than those of individuals not in care and is a source of international concern (Sebba & Luke, 2019; McNamara et al., 2019 ). Despite positive shifts in the legislative landscape to increase focus and support for the educational progress of CYPIC, the attainment gap persists. CYPIC are not a homogenous group, and some go on to do well in education. Therefore, it is important not to make assumptions and to inform decisions affecting the educational experiences of CYPIC from their own perspective. A systematic literature review was conducted to explore the educational experiences of CYPIC living in the United Kingdom in qualitative and mixed-methods literature over the last decade. A total of eleven studies were reviewed, incorporating the views of 203 CYPIC. A process of thematic synthesis was used to illuminate the facilitators and barriers to CYPIC's educational attainment, and four themes were identified: impact of care; support; quality of relationships and agency. The findings of the synthesis are considered with reference to relevant psychological theory and previous research. The limitations of the synthesis are discussed as well as the implications for improvements in service delivery for CYPIC. The review findings are relevant to policy makers and all professionals who work with CYPIC to support their education.